Availability and affordability of cardiovascular disease medicines and their effect on use in high-income, middle-income, and low-income countries: an analysis of the PURE study data - Khatib, Rasha; McKee, Martin; Shannon, Harry; Chow, Clara; Rangarajan, Sumathy; Teo, Koon; Wei, Li; Mony, Prem; Mohan, Viswanathan; Gupta, Rajeev; Kumar, Rajesh; Vijayakumar, Krishnapillai; et al. (The Lancet (British edition), 2016)
WHO has targeted that medicines to prevent recurrent cardiovascular disease be available in 80% of communities and used by 50% of eligible individuals by 2025. We have previously reported that use of these medicines is very low, but now aim to assess how such low use relates to their lack of availability or poor affordability. We analysed information about availability and costs of cardiovascular disease medicines (aspirin, β blockers, angiotensin-converting enzyme inhibitors, and statins) in pharmacies gathered from 596 communities in 18 countries participating in the Prospective Urban Rural Epidemiology (PURE) study. Medicines were considered available if present at the pharmacy when surveyed, and affordable if their combined cost was less than 20% of household capacity-to-pay. We compared results from high-income, upper middle-income, lower middle-income, and low-income countries. Data from India were presented separately given its large, generic pharmaceutical industry. Communities were recruited between Jan 1, 2003, and Dec 31, 2013. All four cardiovascular disease medicines were available in 61 (95%) of 64 urban and 27 (90%) of 30 rural communities in high-income countries, 53 (80%) of 66 urban and 43 (73%) of 59 rural communities in upper middle-income countries, 69 (62%) of 111 urban and 42 (37%) of 114 rural communities in lower middle-income countries, eight (25%) of 32 urban and one (3%) of 30 rural communities in low-income countries (excluding India), and 34 (89%) of 38 urban and 42 (81%) of 52 rural communities in India. The four cardiovascular disease medicines were potentially unaffordable for 0·14% of households in high-income countries (14 of 9934 households), 25% of upper middle-income countries (6299 of 24 776), 33% of lower middle-income countries (13 253 of 40 023), 60% of low-income countries (excluding India; 1976 of 3312), and 59% households in India (9939 of 16 874). In low-income and middle-income countries, patients with previous cardiovascular disease were less likely to use all four medicines if fewer than four were available (odds ratio [OR] 0·16, 95% CI 0·04–0·57). In communities in which all four medicines were available, patients were less likely to use medicines if the household potentially could not afford them (0·16, 0·04–0·55). Secondary prevention medicines are unavailable and unaffordable for a large proportion of communities and households in upper middle-income, lower middle-income, and low-income countries, which have very low use of these medicines. Improvements to the availability and affordability of key medicines is likely to enhance their use and help towards achieving WHO's targets of 50% use of key medicines by 2025. Population Health Research Institute, the Canadian Institutes of Health Research, Heart and Stroke Foundation of Ontario, AstraZeneca (Canada), Sanofi-Aventis (France and Canada), Boehringer Ingelheim (Germany and Canada), Servier, GlaxoSmithKline, Novartis, King Pharma, and national or local organisations in participating countries.